Activated clay of nest structure encapsulated sulfur cathodes for lithium–sulfur batteries. Issue 36 (23rd April 2015) - Cao, Zhaoxia; Ma, Chao; Jia, Yujie; Sun, Zhixian; Yue, Hongyun; Yin, Yanhong; Yang, Shuting
<x xml:space="preserve">Abstract</x> Activated clay (AC) with a nest-like structure and a large surface area was employed to support sulfur as the cathode for lithium–sulfur (Li–S) batteries.